Pengembangan Soal Tes Kemampuan Akademik (TKA) Matematika SMP Menggunakan Konteks Pantai Kalianda Lampung - Harisman Nizar (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2026)
This study aims to develop a Junior High School Mathematics Academic Ability Test (TKA) question based on the Kalianda Beach, Lampung context, that meets the criteria for validity and practicality, and to examine its potential effects on students' mathematical problem-solving abilities. The study applies a development study research design approach, which is implemented through two main stages: preliminary and formative evaluation. Data collection is carried out using several techniques, including walk-throughs, observations, interviews, and tests. The quality of the instrument's validity is determined through an expert review process that assesses the suitability of content, construction, and language aspects, then reinforced by student input in the one-to-one stage regarding the clarity of wording and readability of each item. Furthermore, the level of practicality of the instrument is evaluated in the small group stage, which shows that students are able to understand and work on the questions according to the expected objectives. In the field test stage, student work results indicate that the developed TKA questions have a potential effect in supporting students' mathematical problem-solving abilities.